Comparative evaluation of collapse behavior at different structural levels with different connections. (June 2022) - Zhong, Wei-hui; Tan, Zheng; Meng, Bao; Zheng, Yu-hui; Duan, Shi-chao; Jiang, Cheng
Abstract: This study presents the investigation on the anti-collapse behavior of multi-story structures at different structural levels with different connection types. A three-story composite sub-frame with a weld cover-plated flange (WCPF) connection is quasi-statically tested and subjected to an internal column-removal scenario. The accuracy of the numerical modeling method is verified by quasi-static tests and combined with previous experimental tests on two single-story beam–column assemblies with top-and-seat double web-angle (TSDWA) and WCPF connections; and on a multi-story sub-frame with a TSDWA connection. Based on the modeling method, numerical models considering peripheral frames are established using the hybrid element modeling method, and the effects of different connection types and structural scales on the collapse-resistant performance are analyzed in detail. The results indicate that when the actual boundary restraints are considered, the collapse resistance of multi-story frames can be approximately summed up to derive the total resistance of the single-story beam-column assemblies with TSDWA connections. However, for models with WCPF connections, it is unsafe to apply the collapse resistance of single-story beam-column assemblies to represent that of multi-story planar frames. For a more thorough understanding of the load-resisting mechanisms, the contribution of different resistance mechanisms is quantitatively distinguished by introducing contribution coefficients. Finally, resistance improvement strategies for multi-story planar frames with WCPF and TSDWA connections are proposed. The ultimate load of models with WCPF and TSDWA connections increase by 65% and 76%, respectively, indicating that these strategies are beneficial for the effective exertion of catenary action. Highlights: A three-story sub-frame with weld cover-plated flanges connection was tested. The model predictions and experimental outcomes were in good agreement. Diverse frame stiffness connections and structural scales were utilized and compared. Resistance improvement strategies for multi-story frames are proposed.